(9x^5)/(3x^3)
First divide 9 with 3
9/3 = 3
Remember that when you divide variables, you are really subtracting their exponents.
x^5/x^3 = x^2
Answer: 3x^2
-------------------------------------------------------------------------------------------------------
5/(x-4)
This cannot be simplified, because you'll have to find the parenthesis's total first before dividing.
-------------------------------------------------------------------------------------------------------
(24a^4b^2)/(-2a^3b^5)
24/-2 = -12
a^4/a^3 = a
b^2/b^5 = 1/b^3
Combine the terms
(-12(a))/(b³) = -12a/b³
Answer: -12a/b³
-------------------------------------------------------------------------------------------------------
hope this helps